Underutilized fruit crops as a sustainable approach to enhancing nutritional security and promoting economic growth - Marappan, Kumaresan; Sadasivam, Shakila; Natarajan, Naveena; Arumugam, Vijai Ananth; Lakshmaiah, Kathari; Thangaraj, Meera; Giridhar Gopal, Madhumita; Asokan, Akino (Frontiers in Sustainable Food Systems, 2025)
Underutilized fruit crops hold significant potential for commercial cultivation due to their nutritional benefits, resilience to climatic changes, and increasing consumer demand for exotic and health-beneficial fruits. These crops are appealing for sustainable agriculture because they are resistance to major pest and disease as well as excellent adaptability to marginal areas. However, due to a lack of agronomic understanding, restricted market access, and inadequate research, they continue to be generally ignored in mainstream agriculture. According to recent research, the market for underused fruit crops including dragon fruit, baobab, and west Indian cherry has grown at a pace of 10–15% per year due to growing demand from health-conscious consumer segments. Underutilized fruit crops are rich in essential micronutrients, including vitamin C, dietary fiber, and antioxidants. The underutilized crops exhibit strong resilience to harsh agroecological conditions, such as drought and poor soils, making them ideal candidates for cultivating in areas where conventional crops may fail due to climate change. However, their widespread adoption is hindered by barriers including underdeveloped market systems, insufficient post-harvest infrastructure, and limited consumer awareness. These crops are often relegated to niche markets, with baobab, for instance, currently commanding a growing presence in the global superfood market, valued at USD 60 million in 2017 and projected to reach USD 130 million by 2025. Despite these challenges, the scalability of underutilized fruit crops can be unlocked through targeted interventions such as market development, investments in value-added products, and policy support. With strategic investments in research, extension services, and community-based programs, underutilized fruit crops can move from niche to mainstream markets, contributing to sustainable agricultural development, poverty reduction, and improved food security on a global scale.